159 Delayed-release dimethyl fumarate–associated lymphopenia. Issue 12 (14th November 2019) - Chan, Andrew; Fox, Robert J; Bar-Or, Amit; Chen, Chongshu; Fam, Sami; Gold, Ralf; Hanna, Jerome; Mehta, Devangi; Theodore Phillips, J
Abstract : Introduction: Following the occurrence of one case of progressive multifocal leukoencephalopathy (PML), the dimethyl fumarate (DMF) label was amended in 2015 to recommend treatment interruption for patients with severe, prolonged lymphopenia (SPL, absolute lymphocyte count [ALC] <0.5×10 9 /L ≥6 months). This study examined clinical implications of DMF-associated lymphopenia and post-treatment ALC dynamics in relapsing-remitting multiple sclerosis patients. Methods: Integrated analysis of DMF phase 2b, phase 3, and extension studies was conducted using data from first DMF exposure. ALCs were assessed 4, 8, and 12 weeks after DMF initiation and every 12 weeks thereafter. Results: The analysis population included 2513 patients (DMF exposure up to 11 years). Patients with SPL and those with ALC always above normal had similar incidences of serious infection (0.016 vs 0.010) and herpes zoster (0.000 vs 0.006). One fatal case of PML was associated with SPL (∼3.5 years duration). In patients with mild/moderate lymphopenia and ALC <0.91×10 9 /L at discontinuation (n=138), median time to ALC ≥0.8×10 9 /L was 6 weeks. Conclusions: These data support previous reports that DMF-associated lymphopenia is not correlated with increased incidence of serious or opportunistic infections. For most patients, ALCs increased within 2 months following DMF discontinuation. Support: Biogen. Disclosures to be included on poster.